Global environmental changes: setting priorities for Latin American coastal habitats. (23rd April 2013) - Turra, Alexander; Cróquer, Aldo; Carranza, Alvar; Mansilla, Andrés; Areces, Arsenio J.; Werlinger, Camilo; Martínez‐Bayón, Carlos; Nassar, Cristina Aparecida Gomes; Plastino, Estela; Schwindt, Evangelina; Scarabino, Fabrizio; Chow, Fungyi; et al.
Abstract As the effects of the Global Climate Changes on the costal regions of Central and South Americas advance, there is proportionally little research being made to understand such impacts. This commentary puts forward a series of propositions of strategies to improve performance of Central and South American science and policy making in order to cope with the future impacts of the Global Climate Changes in their coastal habitats.